2022
DOI: 10.1155/2022/2903808
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Ginkgo biloba Extract Combined with Hormones in the Treatment of Sudden Deafness and Its Effect on the Reactivity of Peripheral Blood T Cell Subsets

Abstract: This work was aimed at exploring the efficacy of Ginkgo biloba extract combined with hormones in the treatment of sudden deafness and the influence on the reactivity of peripheral blood T cell subsets (PBTCSs). In this work, 64 patients with sudden deafness who were treated in The First Affiliated Hospital of Hunan University of Traditional Chinese Medicine from August 2019 to August 2022 were selected as the research objects. The patients were randomly divided into a hormone group (treatment with prednisone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Although it is simple to administer, the drug’s interference with the blood–labyrinth barrier makes it challenging to achieve the ideal concentration and duration of action in the inner ear. Increasing the drug dosage or prolonging the medication period may increase the incidence of glucocorticoid-related adverse reactions, thus indicating the treatment’s lack of effectiveness and safety[ 25 , 26 ]. Local administration is a new method proposed to compensate for the deficiencies of systemic administration.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is simple to administer, the drug’s interference with the blood–labyrinth barrier makes it challenging to achieve the ideal concentration and duration of action in the inner ear. Increasing the drug dosage or prolonging the medication period may increase the incidence of glucocorticoid-related adverse reactions, thus indicating the treatment’s lack of effectiveness and safety[ 25 , 26 ]. Local administration is a new method proposed to compensate for the deficiencies of systemic administration.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%